(untitled) (PANGEEA, 2025)
Salciua, the perfect rural. Sălciua is common located in north of Alba County, to the Aries Valley, in the middle of Trascau mountains. Geological structure of the area consists of limestone, so he developed an impressive karstic relief, in surface and underground, complex known as “Vânătare-Huda lui Papară”. Complex name is on two of the most important caves of the Apuseni Mountains. Besides these caves are developing other types of karst terrain. This area provides an important tourism potential, still put in value.